2022
DOI: 10.21037/qims-22-17
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude of low-frequency fluctuations in multiple-frequency bands in patients with intracranial tuberculosis: a prospective cross-sectional study

Abstract: Background Resting-state functional magnetic resonance imaging (rs-fMRI) is widely used to study brain functional alteration, but there have been no reports of research regarding the application of rs-fMRI in intracranial tuberculosis. The purpose of this prospective, cross-sectional study was to investigate spontaneous neural activity at different frequency bands in patients with intracranial tuberculosis using rs-fMRI with amplitude of low-frequency fluctuation (ALFF) and fractional ALFF (fALFF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…This region, part of the primary auditory cortex, could influence the risk of KOA through indirect pathways, perhaps by affecting communication and social interaction abilities that might influence physical activity levels or pain reporting tendencies. The paracentral lobule, part of the primary motor and sensory cortices, plays a role in processing and integrating sensory information from the body ( Kong et al, 2022 ; Zhu et al, 2022 ). Increased volume in these areas might enhance sensory discrimination, potentially contributing to more effective management or perception of osteoarthritic pain.…”
Section: Discussionmentioning
confidence: 99%
“…This region, part of the primary auditory cortex, could influence the risk of KOA through indirect pathways, perhaps by affecting communication and social interaction abilities that might influence physical activity levels or pain reporting tendencies. The paracentral lobule, part of the primary motor and sensory cortices, plays a role in processing and integrating sensory information from the body ( Kong et al, 2022 ; Zhu et al, 2022 ). Increased volume in these areas might enhance sensory discrimination, potentially contributing to more effective management or perception of osteoarthritic pain.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that low-frequency oscillatory activity is thought to be associated with neuronal fluctuations in the cortex, whereas high-frequency oscillations (> 0.08 Hz) mainly reflect white matter signals and are susceptible to interference by physiological noise (Lou et al, 2020b;Kong et al, 2022). Our results indicate that possibly brain stability is better in the slow-4, slow-5 bands and that some brain networks activated in the slow-2-slow-3 band may be dominated by white matter signals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the BOLD signal in fMRI reflects the activation of neurons and global physiological fluctuations [ 93 ], which may influence the estimation of ALFF. The fALFF is a modified index of ALFF that, relative to the ALFF, can improve the sensitivity and specificity to spontaneous neural activities [ 87 , 94 ], may provide us with more sensitive information about low-frequency BOLD fluctuations in WM, and validate abnormal functional neural activity in patients with TIA. However, it is noteworthy that the results of ALFF and fALFF analyses both showed decreased low-frequency neural activities in WM of patients with TIA compared with HCs, which may suggest an impaired function in these motor, emotional, and cognitive-related WM regions caused by TIA onset.…”
Section: Discussionmentioning
confidence: 99%